DAMPAK MOBILITAS TENAGA KERJA TERHADAP PENDAPATAN RUMAH TANGGA PEDESAAN - SRI HERY SUSILOWATI (SOCA: Jurnal Sosial Ekonomi Pertanian, 2005)
Rural-urban migration activity has increased recently. Those activities resulted bothpositive and negative impact to rural economy, especially on household income. The purposeof this study is to learn the impact of rural-urban migration on rural household income. Thestudy is based on PATANAS (Panel Petani Nasional) data of 14 West Java villages in 2001.The study concluded that rural-urban migration has a positive impact both on rural householdincome and rural economic development Total household’s income is significantlyinfluenced by remittance while household’s income comes from migration activity issignificantly influenced by level of education and number of migrate household’s members.